Der Vertrag von Sèvres - Gassner, Miriam (Studien zur Geschichte des Völkerrechts, 2023)
The 1920 Treaty of Sèvres between the Allied Powers and Turkey can undoubtedly be described as one of the most significant international treaties of the 20th century. Aiming at reshaping the Middle East, it laid the foundation for the British Empire to reach the peak of its territorial expansion shortly after it was signed. The fact that the treaty has been little noticed in the German-speaking world is probably also due to the fact that until now there has been no complete translation of the treaty into German. The aim of this work is now to provide such a translation and to place the Treaty of Sèvres in the context of the Paris Peace Treaties.